Using high-resolution data to assess land use impact on nitrate dynamics in East African Tropical Montane Catchments - Jacobs, S.R.; Weeser, B.; Guzha, A.C.; Rufino, Mariana C.; Butterbach-Bahl, Klaus; Windhorst, D.; Breuer, Lutz (Wiley, 2018)
Land use change alters nitrate (NO3‐N) dynamics in stream water by changing nitrogen cycling, nutrient inputs, uptake and hydrological flow paths. There is little empirical evidence of these processes for East Africa. We collected a unique 2 year high‐resolution data set to assess the effects of land use (i.e., natural forest, smallholder agriculture and commercial tea plantations) on NO3‐N dynamics in three subcatchments within a headwater catchment in the Mau Forest Complex, Kenya's largest tropical montane forest. The natural forest subcatchment had the lowest NO3‐N concentrations (0.44 ± 0.043 mg N L−1) with no seasonal variation. NO3‐N concentrations in the smallholder agriculture (1.09 ± 0.11 mg N L−1) and tea plantation (2.13 ± 0.19 mg N L−1) subcatchments closely followed discharge patterns, indicating mobilization of NO3‐N during the rainy seasons. Hysteresis patterns of rainfall events indicate a shift from subsurface flow in the natural forest to surface runoff in agricultural subcatchments. Distinct peaks in NO3‐N concentrations were observed during rainfall events after a longer dry period in the forest and tea subcatchments. The high‐resolution data set enabled us to identify differences in NO3‐N transport of catchments under different land use, such as enhanced NO3‐N inputs to the stream during the rainy season and higher annual export in agricultural subcatchments (4.9 ± 0.3 to 12.0 ± 0.8 kg N ha−1 yr−1) than in natural forest (2.6 ± 0.2 kg N ha−1 yr−1). This emphasizes the usefulness of our monitoring approach to improve the understanding of land use effects on riverine N exports in tropical landscapes, but also the need to apply such methods in other regions.